Pandemic Politics : How COVID-19 Reshaped Political Communication and Voter Engagement Specific for Online Reach (International Journal of Scientific Research in Science and Technology, 2024)
This research paper delves into the effectiveness of these digital strategies, examining their impact on voter behavior and the long-term implications for political engagement. We investigate how politicians and political parties adapted to the new digital landscape, leveraging social media, online advertising, and virtual events to reach voters. The COVID-19 pandemic has accelerated the transition from traditional, face-to-face interactions to digital, hash tag-driven campaigns. This study sheds light on the challenges and opportunities presented by this shift, offering insights into the future of political communication and the role of digital technologies in shaping electoral outcomes.